2017
DOI: 10.1515/cclm-2017-0282
|View full text |Cite
|
Sign up to set email alerts
|

Serum omentin-1 is a novel biomarker for predicting the functional outcome of acute ischemic stroke patients

Abstract: Higher omentin-1 levels at baseline were negatively associated with poor functional outcome among ischemic stroke patients. Omentin-1 may represent a biomarker for predicting poor functional outcome of acute ischemic stroke patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…In line with the preclinical studies, cross-sectional studies reported that circulating omentin concentrations were lower in people with coronary artery disease or ischaemic stroke compared with individuals without cardiovascular disease [10,[35][36][37][38][39][40]. Lower omentin concentrations were also related to less favourable short-term functional outcome in individuals with ischaemic stroke [39].…”
Section: Association Between Omentin and Cardiovascular Outcomesmentioning
confidence: 57%
“…In line with the preclinical studies, cross-sectional studies reported that circulating omentin concentrations were lower in people with coronary artery disease or ischaemic stroke compared with individuals without cardiovascular disease [10,[35][36][37][38][39][40]. Lower omentin concentrations were also related to less favourable short-term functional outcome in individuals with ischaemic stroke [39].…”
Section: Association Between Omentin and Cardiovascular Outcomesmentioning
confidence: 57%
“…With respect to CVD, circulating omentin was decreased in patients with coronary artery disease and appeared to have a protective role in patients with ischaemic stroke . In line, administration of omentin in mice reduced tissue damage after ischaemia/reperfusion and delayed the development of aortic atherosclerotic lesions with reduced vascular inflammation …”
Section: Introductionmentioning
confidence: 72%
“…1 With respect to CVD, circulating omentin was decreased in patients with coronary artery disease 6,7 and appeared to have a protective role in patients with ischaemic stroke. 8,9 In line, administration of omentin in mice reduced tissue damage after ischaemia/reperfusion 10 and delayed the development of aortic atherosclerotic lesions with reduced vascular inflammation. 11 In contrast with the findings from cross-sectional and experimental studies, the prospective analysis within the KORA F4/FF4 cohort indicated that higher circulating omentin is associated with a higher risk of T2D.…”
Section: Introductionmentioning
confidence: 87%
“…Some population studies reported that omentin-1 was significantly associated with carotid atherosclerosis among metabolic syndrome subjects and type 2 diabetes patients 4 , 5 ) . Our previous study has also demonstrated that higher omentin-1 levels at baseline were inversely associated with poor functional outcome among ischemic stroke patients 6 ) . To date, no study has specifically evaluated the association between omentin-1 levels and carotid atherosclerosis among ischemic stroke patients.…”
Section: Introductionmentioning
confidence: 84%